Amendments to the first part of Book VI of the 1983 Code of Canon Law - Mikołajczuk, Krzysztof (Prawo Kanoniczne, 2022)
With the Apostolic Constitution Pascite gregem Dei, Pope Francis promulgated the new Book VI of the Code of Canon Law. The revised Book VI came into force on 8 December 2021 and its promulgation has brought to an end the work started in 2007, when Pope Benedict XVI mandated the Pontifical Council for Legal Texts to revise the penal law of the Church. Book VI (“Penal Sanctions in the Church”), which is of interest to us, consists of two parts: the first part deals with offences and punishments in general, while the other one covers particular offences and penalties established for them. Each part is divided into titles that make up 89 canons in total. The study focuses on the first part entitled “Offences and punishments in general” (canons 1311-1363), which is undoubtedly the richest in meaning – not only because of the concepts it contains, even though the legislator did not intend to provide any definitions in penal law. The first part is divided into six titles. These are: The punishment of offences in general (canons 1311-1312); Penal law and penal precept (canons 1313-1320); Those who are liable to penal sanctions (canons 1321-1330); Penalties and other punishments (canons 1331-1340): Chapter I deals with censures (canons 1331-1335); Chapter II covers expiatory penalties (canons 1336-1338); Chapter III contains regulations on penal remedies and penances (canons 1339-1340); The application of penalties (canons 1341-1353); and The remission of penalties and the prescription of actions (canons 1354-1363